2009
DOI: 10.1038/jid.2009.169
|View full text |Cite
|
Sign up to set email alerts
|

Association between IL13 Polymorphisms and Psoriatic Arthritis Is Modified by Smoking

Abstract: Genetic and environmental factors influence the development of psoriasis (Ps) and psoriatic arthritis (PsA). Recently, we reported that three IL13 polymorphisms, rs1800925, rs20541, and rs848, on chromosome 5q31 conferred the risk for Ps. IL13 encodes IL-13, a Th2 cytokine, and rs1800925 and rs20541 confer risk of asthma. Further, smoking may increase the risk of developing Ps. We examined the association between IL13 polymorphisms, smoking, and PsA in two Ps sample sets genotyped for rs1800925, rs20541, and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
4
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 39 publications
0
48
4
3
Order By: Relevance
“…IL-6 impairs Treg regulation and enables cutaneous T cells to escape from Treg suppression (33), thereby contributing to the poor suppression of T EM cells by Tregs, tipping the balance in favor of pathogenic Th1 and Th17 cells over Tregs. IL-13, a Th2 cytokine, which was shown to confer a modest risk for psoriasis, was also inhibited in our research (34). S100A7, also called psoriasin, belongs to the pleiotropic S100 family of calciumbinding proteins and was identified as a protein upregulated in abnormally differentiated psoriatic keratinocytes (35).…”
Section: Discussionmentioning
confidence: 59%
“…IL-6 impairs Treg regulation and enables cutaneous T cells to escape from Treg suppression (33), thereby contributing to the poor suppression of T EM cells by Tregs, tipping the balance in favor of pathogenic Th1 and Th17 cells over Tregs. IL-13, a Th2 cytokine, which was shown to confer a modest risk for psoriasis, was also inhibited in our research (34). S100A7, also called psoriasin, belongs to the pleiotropic S100 family of calciumbinding proteins and was identified as a protein upregulated in abnormally differentiated psoriatic keratinocytes (35).…”
Section: Discussionmentioning
confidence: 59%
“…IL13 gene polymorphisms influence this relationship. In a recent study, it was shown that the minor alleles (rs1800925*T, rs20541*A, and rs848*A) are associated with protection from PsA versus controls [98]. No association with psoriasis was seen when PsA cases were excluded.…”
Section: Environmental Factorsmentioning
confidence: 97%
“…No association with psoriasis was seen when PsA cases were excluded. Smoking appeared to abrogate this protective effect [98].…”
Section: Environmental Factorsmentioning
confidence: 97%
“…Heinzmann et al (2003), on the other hand, found no correlation between the IL-13 variant Arg110Gln and juvenile idiopathic arthritis compared to the controls. Several studies have indicated that a polymorphism in the IL-13 gene (rs1800925 C/T) was strongly associated with psoriatic arthritis (PsA) (Duffin et al 2009;Bowes et al, 2011;Eder et al, 2011). Moreover, it has been proposed that similar pathogenic mechanisms may be shared among other autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%